2009
DOI: 10.1177/1403494808091343
|View full text |Cite
|
Sign up to set email alerts
|

Dating violence among school students in Tanzania and South Africa: Prevalence and socio-demographic variations

Abstract: DV is prevalent and widespread in the study sites. Violence control policies and interventions should target young adolescents. Since there was not one clearly defined subgroup identified as being at high risk, such programmes should not be limited to high risk groups only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
35
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 105 publications
4
35
0
2
Order By: Relevance
“…[2] Those experiencing IPV may present to healthcare services with physical injury, [3] depression, or suicidal ideation and suicide attempts. [4] Studies worldwide have shown that physical, psychological and sexual violence vary widely across countries and have been reported in 10 -50% of relationships for individuals aged up to 19 years, including in the USA, India, Nigeria, China, [5] the UK, [6,7] Tanzania [8] and South Africa (SA). [5,8,9] Most studies have reported that psychological violence is most common, followed by physical violence and then sexual violence.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…[2] Those experiencing IPV may present to healthcare services with physical injury, [3] depression, or suicidal ideation and suicide attempts. [4] Studies worldwide have shown that physical, psychological and sexual violence vary widely across countries and have been reported in 10 -50% of relationships for individuals aged up to 19 years, including in the USA, India, Nigeria, China, [5] the UK, [6,7] Tanzania [8] and South Africa (SA). [5,8,9] Most studies have reported that psychological violence is most common, followed by physical violence and then sexual violence.…”
mentioning
confidence: 99%
“…[4] Studies worldwide have shown that physical, psychological and sexual violence vary widely across countries and have been reported in 10 -50% of relationships for individuals aged up to 19 years, including in the USA, India, Nigeria, China, [5] the UK, [6,7] Tanzania [8] and South Africa (SA). [5,8,9] Most studies have reported that psychological violence is most common, followed by physical violence and then sexual violence. [10,11] Risk factors for perpetration and victimisation of IPV in adolescent relationships also vary between countries, and associations with higher age, [12] not being raised by a biological mother, [11] higher maternal education, [8] substance use, particularly alcohol, [9,11,13] previous maltreatment, violence in the home and aggressive peer networks, [10] especially at school, [13] and attitudes supportive of male superiority, [6,9] and for girls having an older partner, [8,10] have been reported.…”
mentioning
confidence: 99%
See 3 more Smart Citations